Enhancement of biodegradation and detoxification of methylene blue by preformed biofilm of thermophilic bacilli on polypropylene perforated balls - Zammuto, Vincenzo; Macrì, Angela; Agostino, Eleonora; Ruggeri, Lorenzo María; Caccamo, María Teresa; Magazù, Salvatore; Campos, Víctor L.; Aguayo Venegas, Paulina Andrea.; Guglielmino, Salvatore; Gugliandolo, Concetta (MDPI, 2024)
Microbial degradation represents an eco-friendly alternative to traditional physicochemical treatments in removing persistent and toxic environmental pollutants, including synthetic dyes (i.e., methylene blue, MB) employed in different industries. The exploitation of thermophilic bacilli, such as those isolated from the shallow hydrothermal vents of the Eolian Islands (Italy), could provide valuable resources for the treatment of warm, dye-containing wastewater. In this study, we evaluated the ability of preformed biofilms on polypropylene perforated balls (BBs) of fifteen thermophilic bacilli, to decolor, degrade, and detoxify MB in aqueous solutions. Among them, BBs of Bacillus licheniformis B3-15 and Bacillus sp. s7s-1 were able to decolorize MB more than 50% in saline solution (NaCl 2%), incubated in static conditions at 45 °C for 48 h. At optimized initial conditions (10 mg L−1 MB, pH 5.2 for B3-15 or pH 4 for s7s-1), the two strains enhanced their decolorization potential, reaching 96% and 67%, respectively. As indicated by ATR-FTIR spectroscopy, the treatment with BB B3-15 was the most efficient in degrading the Cl–C and –NH groups of MB. This degraded solution was 40% less toxic than undegraded MB, and it has no impact on the bioluminescence of Vibrio harveyi, nor the growth of the marine diatom Phaeodactylum tricornutum. Biofilm formed by strain B3-15 on polypropylene perforated balls could be proposed as a component of bioreactors in the treatment of warm, dye-containing wastewater to concomitantly remediate MB pollution and simultaneously counteract harmful effects in aquatic environments.
Keywords: Biofilms; Decolorization; Degradation; Thermophiles; Biorremediación; Azul de metileno